SAT0139 AGE-BASED (<65 VS ≥65 YEARS) INCIDENCE OF INFECTIONS AND SERIOUS INFECTIONS IN TOFACITINIB-, ADALIMUMAB- AND PLACEBO-TREATED PATIENTS WITH RHEUMATOID ARTHRITIS: A POST HOC ANALYSIS OF PHASE 2, PHASE 3 AND PHASE 3B/4 TOFACITINIB STUDIES. (2nd June 2020) - Winthrop, K.; Gold, D.; Henrohn, D.; Wang, L.; Shapiro, A.; Shi, H.; Citera, G.; Schulze-Koops, H.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). A recent ad hoc safety analysis (as of August 2019; may be subject to change) from an ongoing, open-label, randomised, post-authorisation safety study, Study A3921133 (NCT02092467 ), conducted in RA patients (pts) aged ≥50 years with ≥1 cardiovascular risk factor has shown that incidence rates (IRs) of serious infection events (SIEs) were higher with tofacitinib 10 mg BID vs tumour necrosis factor inhibitors (TNFi; adalimumab [ADA] and etanercept) and this difference was more pronounced in pts aged ≥65 years (Pfizer Inc; data on file). Objectives: To assess the IRs of overall infection events and SIEs in pts from Phase (P)2, P3 and P3b/4 tofacitinib RA trials which had a TNFi (ADA) active control or comparator arm. Methods: This is a post hoc analysis of Month 0–12 data pooled from P2 (A3921035; NCT00550446 [first 12-week randomised parallel treatment period only]), P3 (ORAL Standard; NCT00853385 ) and P3b/4 (ORAL Strategy; NCT02187055 ) studies. Pts randomised to receive tofacitinib 5 mg BID, tofacitinib 10 mg BID, ADA 40 mg subcutaneously every other week and placebo (PBO) were included and assessed overall and by age (<65 or ≥65 years). SIEs were defined as infections requiring hospitalisation or parenteral antimicrobial therapy, or meeting other criteria for a serious adverse event. IRs (pts with events/100 pt-years of exposure [PY]) and 95% confidence intervals (CIs) were calculated for all infection events and SIEs; only the first infection events that occurred up to 28 days after the last dose or to the data cut-off date were considered. Results: Of 2180 pts included in the pooled studies (tofacitinib 5 mg BID: N=1064 [943.4 PY]; tofacitinib 10 mg BID: N=306 [236.6 PY]; ADA: N=643 [554.3 PY]; PBO: N=167 [108.1 PY]), 1841 (84.4%) were aged <65 years and 339 (15.6%) were aged ≥65 years. In general, the IRs for all infection events and SIEs were higher with tofacitinib 5 mg BID, tofacitinib 10 mg BID and ADA in pts aged ≥65 years compared with pts aged <65 years. Overall and when stratified by age, IRs for all infection events were similar across the active treatment groups (Figure 1 ); IRs with PBO were lower vs the active treatment groups overall and in pts aged <65 years, and numerically lower vs the active treatment groups in pts aged ≥65 years. IRs for SIEs were comparable across active treatment groups in pts aged <65 years, while among pts aged ≥65 years, IRs were numerically higher for tofacitinib 10 mg BID vs ADA, and appeared to be similar for tofacitinib 5 mg BID and ADA (Figure 2 ). Conclusion: In this analysis of data pooled from P2, P3 and P3b/4 tofacitinib RA studies which included a TNFi arm (ADA), the risk of SIEs or infections overall was similar for tofacitinib and ADA with the exception of a numerically higher rate of SIEs with tofacitinib 10 mg BID vs ADA in pts aged ≥65 years. In most countries, tofacitinib 10 mg BID is not an approved dose for the treatment of RA. This post hoc comparison is limited by variation in sample size and PY of exposure between treatment and age groups, and a small number of cases of SIEs in the ≥65-year age group resulting in wide 95% CIs; interpretation of results should be made with caution. The findings in the present analysis are consistent with increasing age being a known risk factor for infections. Acknowledgments: Study sponsored by Pfizer Inc. Medical writing support was provided by Christina Viegelmann of CMC Connect and funded by Pfizer Inc. Disclosure of Interests: Kevin Winthrop Grant/research support from: Bristol-Myers Squibb, Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, Galapagos, Gilead, GSK, Pfizer Inc, Roche, UCB, David Gold Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Dan Henrohn Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Lisy Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Andrea Shapiro Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Harry Shi Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Gustavo Citera Grant/research support from: AbbVie, Amgen, Eli Lilly, Gema, Genzyme, Novartis and Pfizer Inc, Consultant of: AbbVie, Amgen, Eli Lilly, Gema, Genzyme, Novartis and Pfizer Inc, Hendrik Schulze-Koops Grant/research support from: Pfizer Inc